The effects of wind farm wakes on freezing sea spray in the mid-Atlantic offshore wind energy areas - D. Rosencrans; D. Rosencrans; J. K. Lundquist; J. K. Lundquist; J. K. Lundquist; M. Optis; M. Optis; N. Bodini (Wind Energy Science)
The USA is expanding its wind energy fleet offshore where winds tend to be strong and consistent. In the mid-Atlantic, strong winds, which promote convective heat transfer and wind-generated sea spray, paired with cold temperatures can cause ice on equipment when plentiful moisture is available. Near-surface icing is induced by a moisture flux from sea spray, which poses a risk to vessels and crews. Ice accretion on turbine rotors and blades occurs from precipitation and in-cloud icing at temperatures below freezing. Ice accretion induces load and fatigue on mechanical parts, which reduces blade performance and power production. Thus, it is crucial to understand the icing hazard across the mid-Atlantic. We analyze Weather Research and Forecasting model numerical weather prediction simulations at a coarse temporal resolution over a 21-year period to assess freezing sea spray (FSS) events over the long-term record and at finer granularity over the 2019–2020 winter season to identify the post-construction turbine impacts. Over the 2019–2020 winter season, results suggest that sea-spray-induced icing can occur up to 67 h per month at 10 m at higher latitudes. Icing events during this season typically occur during cold air outbreaks (CAOs), which are the introduction of cold continental air over the warmer maritime surface. During the 2019–2020 winter season, CAOs lasted a total duration of 202 h. While not all freezing sea spray events occurred during CAOs over the 21-year period, all CAO events had FSS present. Further, we assess the turbine–atmosphere impacts of wind plant installation on icing using the fine-scale simulation dataset. Wakes from large wind plants reduce the wind speed, which mitigates the initiation of sea spray off white-capped waves. Conversely, the near-surface turbine-induced introduction of cold air in frequent wintertime unstable conditions enhances the risk for freezing. Overall, the turbine–atmosphere interaction causes a small reduction in FSS hours within the wind plant areas, with a reduction up to 15 h in January at the 10 and 20 m heights.